2014
DOI: 10.1016/j.ssci.2014.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Research into cases of slips, collisions and other movement disturbances occurring in work situations in a hospital environment

Abstract: 2Research into cases of slips, collisions and other movement disturbances occurring in work situations in a hospital environment Abstract Slips, collisions and other accidental movement disturbances are very common in work situations and occur in every occupational activity sector. Research into these accidents was conducted at a hospital, based on analysing collectively and in-depth cases of accidents involving movement disturbance. This revealed accident factors of various types as closely associated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
1
0
4
Order By: Relevance
“…It is notable that slipping has been a particular area of attention, forming a large part of the discussions at STF symposia over the years, for example, at the Liberty Mutual Research Institute for Safety international symposium on the measurement of slipperiness (Courtney et al 2001a). Some researchers have, however, suggested that use of the ‘slips, trips and falls’ terminology and the tendency to focus on slipping fail to give sufficient recognition to other important causes of injuries on level surfaces involving loss of balance (Lortie and Rizzo 1999) or movement disturbance (Leclercq, Monteau, and Cuny 2010; Leclercq et al 2014; Leclercq et al 2015). …”
Section: Definitions and Scopementioning
confidence: 99%
“…It is notable that slipping has been a particular area of attention, forming a large part of the discussions at STF symposia over the years, for example, at the Liberty Mutual Research Institute for Safety international symposium on the measurement of slipperiness (Courtney et al 2001a). Some researchers have, however, suggested that use of the ‘slips, trips and falls’ terminology and the tendency to focus on slipping fail to give sufficient recognition to other important causes of injuries on level surfaces involving loss of balance (Lortie and Rizzo 1999) or movement disturbance (Leclercq, Monteau, and Cuny 2010; Leclercq et al 2014; Leclercq et al 2015). …”
Section: Definitions and Scopementioning
confidence: 99%
“…Par exemple, une infirmière porte une attention particulièrement soutenue à son activité lorsqu'elle assiste un médecin intervenant auprès d'un patient en grand danger. À ce moment-là, si son mouvement est gêné par le câble d'un équipement, on peut penser que le risque que ce mouvement soit perturbé puisse être plus élevé que lorsque l'exigence de sa tâche en termes d'attention est moins élevée (Leclercq et al, 2014). Le risque de perturbation du mouvement est également plus élevé lorsqu'un travailleur doit à un moment donné effectuer une tâche de surveillance visuelle tout en se déplaçant puisqu'il peut ne pas lui être possible d'anticiper un obstacle sur son parcours (Leclercq et al, 2017).…”
Section: Variabilité Au Sein Des Situations Et Régulationunclassified
“…Sa contribution à la prévention du ralentissement ou de l'arrêt du processus de production le conduit parfois à élargir le périmètre du système contrôlé en apportant son aide à un collègue en difficulté par exemple. Les travaux sur les APM montrent que nombre d'entre eux se sont produits lorsque le travailleur s'engage dans une soustâche, suite à un incident technique (Abdat et al, 2014) ou suite à une interruption (Leclercq et al, 2014) et fenêtres, etc.). La prévention des APM, en particulier de ceux qui se produisent au cours de la réalisation de mouvements qui sont nécessaires à la tâche réalisée tout en n'étant pas spécifiques à cette tâche (un déplacement à pied par exemple), bénéficierait de la mise en visibilité des interactions travailleurs/enveloppe physique de travail et de la compréhension des régulations (1) ayant un impact sur ces interactions et/ou (2) ayant conduit à leur perturbation ou leur absence de perturbation.…”
Section: La Gestion Du Temps Et Le Risque D'apmunclassified
See 2 more Smart Citations